2012
DOI: 10.1016/j.physio.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Physiotherapy strategies for a woman with symphysis pubis diastasis occurring during labour

Abstract: This case report demonstrates a therapeutic exercise program as a noninvasive functional treatment for symphysis pubis diastasis (SPD) and reports its results. A 32-year-old primigravida with SPD during labour received a specific functional exercise program, which consisted of abdominal stabilization and strengthening of the pelvic floor muscles, hip adductors, and extensors; training for bed mobility; and walking training with suitable aids. The program was performed for 1-hour per session, twice a day, for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 10 publications
0
15
0
7
Order By: Relevance
“…The present systematic review found use of physiotherapy as the main component of conservative treatment for the majority of women with SPD [1,4,7,10,12,[18][19][20][21]24,[27][28]. Most of the studies employed physiotherapy for walking reeducation, mobilization under supervision, and/or strengthening the core muscles, although only two studies detailed the stabilizing and/or strengthening exercises [10,15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present systematic review found use of physiotherapy as the main component of conservative treatment for the majority of women with SPD [1,4,7,10,12,[18][19][20][21]24,[27][28]. Most of the studies employed physiotherapy for walking reeducation, mobilization under supervision, and/or strengthening the core muscles, although only two studies detailed the stabilizing and/or strengthening exercises [10,15].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies employed physiotherapy for walking reeducation, mobilization under supervision, and/or strengthening the core muscles, although only two studies detailed the stabilizing and/or strengthening exercises [10,15]. However, the start of the physiotherapeutic treatment varied from the 2nd to the 14th day after labor [1,[24][25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations